Analysis of Library Services for Persons with Disabilities at the Department of Library And Archives of the Province Of North Sumatra - Rabita, Eva (Edulib, 2021)
Persons with disabilities have a legal position and the same human rights as Indonesian citizens, including obtaining and utilizing public services. Library and archive services of Sumatera Utara as a public institution that is useful in meeting the needs of education, research, preservation, information, and recreation for visitors regardless of disabilities. This research was conducted to determine the library in facilitating persons with disabilities in physically accessing the library and special services for information sources on disabilities. Based on the objectives and form of the problem in this study, the research design uses mixed methods. The instrument used in this study was the itemS of the International Federation Library Association and Institution (IFLA) standard and supported by the interview questions to the informants. The results of this study explain that accessibility for persons with disabilities in the library has not fully met the criteria, with an average gain of 0.37 (almost inappropriate)